Hepatitis B surface antigen and hepatitis B RNA changes in HIV/hepatitis B virus co-infected participants receiving hepatitis B virus-active antiretroviral therapy. (1st June 2022) - Hawkins, Claudia; Kang, Minhee; Bhattacharya, Debika; Cloherty, Gavin; Kuhns, Mary; Matining, Roy; Thio, Chloe; Samaneka, Wadzanai; Chinula, Lameck; Mulinda, Nyirenda; Badal-Faesen, Sharlaa; Sugandhavesa, Patcharaphan; et al.
Abstract : Introduction: With advances in hepatitis B virus (HBV) therapies, there is a need to identify serum biomarkers that assess the HBV covalently closed circular DNA (cccDNA) reservoir and predict functional cure in HIV/HBV co-infection. Methods: In this retrospective study, combining samples from HIV/HBV co-infected participants enrolled in two ACTG interventional trials, proportions achieving HBsAg less than 0.05 log10 IU/ml and HBV RNA less than log10 1.65 U/ml or not detected (LLoQ/NEG) in response to DUAL [tenofovir TDF+emtricitabine (FTC)] vs. MONO [FTC or lamivudine (3TC)] HBV-active ART, were measured. Predictors of qHBsAg less than 0.05 log10 IU/ml were evaluated in logistic regression models. Results: There were 88 participants [58% women, median age 34; 47 on DUAL vs. 41 on MONO HBV-active ART]. Twenty-one percent achieved HBsAg less than 0.05 log10 IU/ml (30% DUAL vs. 10% MONO). Time to HBsAg less than 0.05 log10 IU/ml was lower (P = 0.02) and the odds of achieving HBsAg less than 0.05 log10 IU/ml were higher (P = 0.07) in DUAL participants. HBV RNA became less than LLoQ/NEG in 47% (DUAL 60% vs. MONO 33%). qHBsAg less than 3 log10 IU/ml was the strongest predictor of HBsAg less than 0.05 log10 IU/ml. Conclusion: This study supports current recommendations of TDF-based DUAL-HBV active ART for initial use in HIV/HBV co-infection. HBV RNA could be a useful marker of treatment response in HIV/HBV co-infected patients on HBV-active ART.